2017
DOI: 10.1021/acsami.6b15902
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Dewetting of Organic Semiconductor Films: The Case of Dinaphthothienothiophene (DNTT) at Dielectric Interfaces

Abstract: The novel organic semiconductor dinaphthothienothiophene (DNTT) has gained considerable interest because its large charge carrier mobility and distinct chemical robustness enable the fabrication of organic field effect transistors with remarkable long-term stability under ambient conditions. Structural aspects of DNTT films and their control, however, remain so far largely unexplored. Interestingly, the crystalline structure of DNTT is rather similar to that of the prototypical pentacene, for which the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 67 publications
4
45
0
Order By: Relevance
“…Therefore, the film structure results from a minimization of the surface free energy of the films which favors the formation of planes where molecules are densely packed, as shown schematically in Figure . This is the (001) surface which exhibits the highest coordination of the DNTT molecules like it is formed on SiO 2 . Interestingly, the work function changes for DNTT monolayers are rather similar in all cases, but are dominated by the choice of the metal substrate.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, the film structure results from a minimization of the surface free energy of the films which favors the formation of planes where molecules are densely packed, as shown schematically in Figure . This is the (001) surface which exhibits the highest coordination of the DNTT molecules like it is formed on SiO 2 . Interestingly, the work function changes for DNTT monolayers are rather similar in all cases, but are dominated by the choice of the metal substrate.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, we note that controlling the molecular orientation and film structure is decisive for the realization of horizontal as well as vertical OFETs since the highly anisotropic electronic properties of the DNTT films result in strongly different device characteristics for varied orientations. Moreover, the distinct dewetting introduces an additional complication to the realization of devices since the current paths may be interrupted …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed interface studies were enabled using highly ordered single crystals as substrates, which were employed to monitor the dynamics of film growth and microscopic diffusion processes as well as post-deposition structural changes. [183,184] Furthermore, pentacene (PEN) and perylene were exploited for excitonic studies of the various crystalline phases, [185,186] with temperature-dependent studies revealing exciton energy shifts as a consequence of strain at interfaces. [187,188] Additionally, individual molecular domains were probed optically for hetero-epitaxial organic films of perfluoropentacene (PFP) on alkali halide substrates.…”
Section: Nanoscale Systems and Characterization Techniquesmentioning
confidence: 99%
“…Recent studies revealed the distinctive structural features of DNTT such as interfacial layer formation and spontaneous molecular rearrangement. [34,35] Such a development underlines that additional verification is required to establish in-depth understanding of this particular semiconductor's morphology.…”
Section: Film Morphologymentioning
confidence: 99%